Ontologia para classificação de perfis de disfagia e terapia nutricional - Sousa, Maria Bernadete Morais de (Universidade Federal Rural do Semi-Árido, 2019)
A dysphagia, also condemned by dysphagic disturbance, should not be considered a doma, but a mutation should not be swallowed or swallowed by a traumatic brain injury, cerebral vascular accident, death, neuromuscular dozen, prolonged gold-tracheal intubation câncer de cabeça e pescoço, raising several health problems or death to death in some cases. Therefore, a multidisciplinary team is normally necessary to monitor patients who are willing to take action and take immediate measures, it will be necessary. This team included doctors, nurses, nutritionists and speech therapists. At the triagem começa phase with an avaliação feita by a nurse or a doctor, who recognizes any abnormality, depending on two symptoms and causes, he asks for some exams to find or change his path or patient for a nutritionist or speech therapist. In this context, this work proposes an ontology to treat dysphagia and recommend nutritional advice for the patient. Ontology and preenchida with input data, including causes, symptoms, types of food consistency (for example, solid, liquid and pasty), as well as types of nutrients (carbohydrates, proteins and fibers). O conhecimento de saída gerado pela ontologia compreende or level of dysphagia of individual patients and a corresponding permitted diet. A methodology used for the development of ontology foi a methodology 101. O model of ontology foi specified with the Ferramenta Protégé, based on the OWL language, which allows automatic verification of the consistency of the model. At the end of the final classification supported by the ontology and an indication of its usefulness in future centers, the area of implementation of medical devices.
Monografia
Keywords: Ontologia; Disfagia; Nutrição; Ontology; Dysphagia; Nutrition; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO::SISTEMAS DE INFORMACAO